Green supply chain practices and supply chain performance in the beverage industry of South Africa - Mahlatsi, Michael Kgaisi (Vaal University of Technology, 2020)
In South Africa, the beverage industry is perceived to be a major contributor to the economy. Internal and external stakeholders in this industry are engaged in environmental collaboration with each other to achieve better environmental and supply chain performance. The aim of this study was to investigate the influence of green supply chain management practices on environmental performance and supply chain performance in the beverage industry of South Africa. It considers four of these practices, namely, internal environment management, investment recovery, eco-design and green purchasing. A quantitative approach was adopted, with the use of a survey questionnaire to collect information from 373 supply chain management professionals from beverage companies in South Africa. The study used a probability simple random sampling method. The data gathered was analysed using the Statistical Package for the Social Sciences (SPSS) version 25.0 and Analysis of a Moment Structures (AMOS) version 25.0. A Confirmatory Factor Analysis (CFA) was used to validate the measurement scales while Structural Equation Modelling (SEM) was applied to test the relations between constructs. The results revealed that internal environment management, investment recovery, eco-design and green purchasing positively and significantly influence environmental performance. Moreover, the results also revealed that environmental performance exerted a strong, significant and positive influence on supply chain performance. Recommendations and implications for further research were made based on these results. The study presents supply chain management professionals, internal and external stakeholders within the beverage industry with useful insights on key factors that ought to be addressed in order to improve their organisational strategies. Therefore, the study is essential to internal and external stakeholders in the beverage industry who wish to improve environmental and supply chain performance.
M. Tech. (Department of Logistics Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Internal environment management; Investment recovery; Eco-design; Green purchasing; Environmental performance; Supply chain performance; Dissertations, Academic -- South Africa; Business logistics; Physical distribution of goods; Green products -- South Africa